Exploring water absorption behaviors on mechanical properties of wheat straw-glass fiber hybrid composites for sustainable engineering solutions - Silvina Siddika Shifa; Md Mehedi Hasan Kanok; Mohammad Salman Haque (Hybrid Advances)
The study explores the enhancement of epoxy composite performance by adding glass fiber and wheat straw, revealing improved tensile strength and hardness compared to unreinforced epoxy. Using a hand-layup procedure, glass fibers and wheat straw are incorporated unidirectionally into an epoxy resin matrix. This study aims to explore how different fiber volume fractions and moisture absorption over two months affect the tensile strength and hardness of hybrid composites. The tensile strength and hardness of weathered specimens are found to be lower values than those of raw samples because of the degradation of the structural integrity of the fibers during water absorption. After being exposed to water, the tensile strength was 20 wt % fiber composite sample was reduced by roughly 32.43 %. A marginal decline in hardness of 5.63 % occurred for 20 wt % hybrid composite. The morphology of the composites after the tensile test and the interactions between the fibers and the epoxy matrix in the as-cast and weathered samples were investigated using SEM. Perfect fiber-matrix bonding was apparent in as-cast composites. However, fiber swellings and de-bonding in the fiber matrix due to voids and moisture absorption were observed in weathered specimens, which reduced the tensile strength and hardness.